2019
DOI: 10.1002/pssa.201900247
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Defects in Diamond by Etch‐Pit Formation

Abstract: Correlation between the reverse current density J R of diamond vertical Schottky barrier diodes (SBD) and the shape of the etch pits is investigated. Etch pits form throughout the whole epitaxial layer area with a density of 6.8 Â 10 4 -3.0 Â 10 5 cm À2 . Most etch pits are isolated-type, with flat-bottom or point-bottom shape. A typical pit size is 3-5 μm in width and 1-3 μm in depth. Some etch pits aggregate linearly with a size of >10 μm. The SBDs show large J R when these etch pit clusters appear. The etch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Shimaoka et al recently reported that aggregated dislocation clusters, not isolated dislocations, are possible killer defects inducing large I leak . 17) The large leakage current was observed irrespective of the position of growth sectors originating from HPHT-grown crystals. The influence of growth sector boundaries for device properties has not been clarified in the present investigation.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Shimaoka et al recently reported that aggregated dislocation clusters, not isolated dislocations, are possible killer defects inducing large I leak . 17) The large leakage current was observed irrespective of the position of growth sectors originating from HPHT-grown crystals. The influence of growth sector boundaries for device properties has not been clarified in the present investigation.…”
Section: Resultsmentioning
confidence: 90%
“…12,13) One of the primary concerns limiting capability is the presence of killer defects which induce Ohmic-like leakage at relatively low reverse voltage. 14,15) The presence of dislocations or dislocation bundles, 16,17) B complex, 18,19) and B aggregation are considered possible causes of such leaky diodes. Suppression of these killer defects is a key issue in enhancing high-current operation with large Schottky contacts.…”
Section: Introductionmentioning
confidence: 99%
“…[ 8 ] On the other hand, some dislocations may extend from the p‐type substrate to the n‐type diamond layer, resulting in extra leakage paths. [ 9 ] In addition, some nonepitaxial crystallites defects [ 10 ] or impurities in the intrinsic layer also can induce shunt conduction paths for reverse current leakage. Figure 2b shows a representative result of C – V measurements at room temperature with a frequency of 10 kHz.…”
Section: Resultsmentioning
confidence: 99%